The mathematics teacher in the digital era an international perspective on technology focused professional development - Clark-Wilson, Alison; Robutti, Ornella; Sinclair, Nathalie (Mathematics education in the digital era)
This volume addresses the key issue of the initial education and lifelong professional learning of teachers of mathematics to enable them to realize the affordances of educational technology for mathematics. With invited contributions from leading scholars in the field, this volume contains a blend of research articles and descriptive texts. In the opening chapter John Mason invites the reader to engage in a number of mathematics tasks that highlight important features of technology-mediated mathematical activity. This is followed by three main sections ? an overview of current practices in teachers' use of digital technologies in the classroom and explorations of the possibilities for developing more effective practices drawing on a range of research perspectives (including grounded theory, enactivism and Valsiner's zone theory). ? a set of chapters that share many common constructs (such as instrumental orchestration, instrumental distance and double instrumental genesis) and research settings that have emerged from the French research community, but have also been taken up by other colleagues. ? meta-level considerations of research in the domain by contrasting different approaches and proposing connecting or uniting elements.